The Private Provision of Infrastructure : Opportunities for Emerging Markets - Grishin, Vadim; Walton, Tom (International Finance Corporation, Washington, DC, 2018)
Infrastructure is the backbone of every economy. It delivers basic services critical to sustainable economic growth, improved living standards, and shared prosperity. The traditional role of financing and operating infrastructure projects has been shaken up in recent decades by the emergence of Public-Private Partnerships. Designed and implemented correctly, these partnerships can bring greater efficiency and sustainability to the provision of public services such as water and sanitation, electric power, transport, and telecommunications.